Examining the (in)compatibility of formal project report writing and notions of agency and creativity in the written work of chemistry majors at a Singaporean university - Toh, Glenn (2022)
I set out in this article to address the question of whether it is possible to be creative and agentive when the written content involves information of a factual, statistical, or empirical nature. In examining the matter of creativity and agentivity in such writing, I seek to locate my understanding of both areas in the realm of the situated, subjective, and the reflexive, and the expression of creativity as an enactment and enablement of these three qualitative dimensions through(out) the fluidity and contingency of the composing process and experience. My discussion first provides an account of my own reflexive positioning as a writing teacher. This section is followed by a review of relevant literature in the area of academic literacies and the way knowledge and disciplinarity as they are captured and naturalized in written text may be challenged for their supposed representation of static and depersonalized views of meaning. Thereafter I consider PW308 – a course in scientific project report writing – and feedback from a group of third-year chemistry students with respect to the situatedness of their individual experiences as they went about composing their project report.